Incidence and Clinical Practice of Myopic Macular Neovascularization: A Nationwide Population-Based Cohort Study - Masahiro Akada, MD; Masahiro Miyake, PhD, MPH; Masayuki Hata, MD, PhD; Ai Kido, MD, PhD; Wakako Okayama, MD; Ai Nakata, MD; Shinya Nakao, MD; Kazuya Morino, MD; Shota Yasukura, MD; Yuki Mori, MD, PhD; Hiroshi Tamura, PhD, ScM; Akitaka Tsujikawa, MD, PhD (Ophthalmology Science)
Purpose: To elucidate the epidemiological background of myopic macular neovascularization (mMNV), including its incidence and treatment patterns. Design: A population-based cohort study using a nationwide claims database. Participants: Individuals covered by the Japanese National Health Insurance System between 2016 and 2022. Methods: This study utilized data from the national claims database managed by the Japan Ministry of Health, Labour and Welfare. The database covers over 95% of health care claims in Japan under the universal health coverage system. We identified individuals with new-onset mMNV between January 2016 and December 2022. We also calculated incidence rates based on age and sex stratification for each year. We also assessed the initial treatment patterns for mMNV, focusing on the use of anti-VEGF therapy. Main Outcome Measures: Incidence rates and treatment patterns of mMNV. Results: During the 7-year period, we identified 45 671 cases of mMNV, with 70.7% occurring in women. The crude incidence rate (per 100 000 person-years) in the general population was 5.17 (95% confidence interval [CI], 5.13–5.22), with 3.12 (95% CI, 3.07–3.18) in men and 7.12 (95% CI, 7.04–7.19) in women. The mean age of onset was lower in men (59.3 ± 16.7 years) than in women (63.5 ± 16.2 years). In total, 52.6% of newly diagnosed patients with mMNV received anti-VEGF treatment, with 43.5% receiving ranibizumab and 56.5% receiving aflibercept. The number of injections in the first (0–12 months), second (13–24 months), and third (25–36 months) years after the initial injection was 2.45 ± 1.83, 0.62 ± 1.42, and 0.46 ± 1.27, respectively. Conclusions: This study provides the largest population-based evidence on the detailed epidemiology of mMNV following the implementation of anti-VEGF therapy under the Japanese National Insurance System. We examined how the incidence varied over time and analyzed the usage rates of each anti-VEGF agent, as well as the number of injections, offering valuable insights into the medical and social implications of mMNV following the widespread implementation of anti-VEGF therapy. These findings enhance understanding of the medical and social features of mMNV. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.